One-Dimensional Azido-bridged Copper(II) Coordination Polymer with Taurine Schiff Base: Syntheses, Structure and IR Spectrum Studies - Xu, Shuqing; Li, Jiaming (Asian Journal of Chemistry, 2011)
The azido-bridged copper(II) complex with composition [Cu(pmt)(N3)]n [pmtH = N-(2- pyridylmethylidene)taurine] has been synthesized and characterized by elemental analysis, IR and single-crystal X-ray diffraction. The crystal of the present complex crystallizes in a monoclinic system, space group P21/c, with a = 7.8108(10), b = 18.1233(19), c = 8.2006(10) Å, b = 94.976(6)º, V = 1156.5(2) Å3, Mr = 318.80, Dc = 1.831 g/cm3, μ = 2.077 mm-1, F(000) = 644, Z = 4, the final R = 0.0506 and wR = 0.1059 for 2147 observed reflections with I > 2s(I). Each Cu(II) atom is six-coordinated to two oxygen and four N atoms with a distorted 4+2 octahedral geometry. The two kinds of cycles with sharing Cu apex are alternately created and interconnected to an interesting 1-D zigzag chain propagating along the c axis. Also, the significant weak CH… N hydrogen bond and p-p stacking interactions between the adjacent chains expanded the 1-D structure to 2-D network in the bc plane and stabilize the packing.